SEX DIFFERENCES IN QUALITY OF LIFE IN PATIENTS WITH ISCHEMIA WITH NO OBSTRUCTIVE CORONARY ARTERIES (INOCA): A PATIENT SELF-REPORT SURVEY FROM INOCA INTERNATIONAL - Sachini Ranasinghe, MD MPH; Najah Khan, MD; C. Noel Bairey Merz, MD; Janet Wei, MD; Maria George; Colin Berry, MD; Alaide Chieffo, MD; Paolo G Camici, MD; Filippo Crea, MD; Juan-Carlos Kaski, DSc, MD; Mario Marzilli, MD; Martha Gulati, MD MS (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD in Women Background: Women with obstructive coronary artery disease (CAD) have a relatively lower quality of life (QoL) compared to men but our understanding of sex differences in QoL in ischemia with no obstructive coronary artery disease (INOCA) is limited. Methods: We conducted a survey of patient members of INOCA International with an assessment of self-reported health measures. Functional capacity was retrospectively estimated using the Duke Activity Status Index (DASI) assessing levels of activities performed before and after INOCA symptom onset. Results: Of the 1579 patient members of INOCA International, the overall survey completion rate was 21%. Women represented 91% of the respondents. Estimated functional capacity, expressed as metabolic equivalents (METs), was higher before compared to after INOCA diagnosis for comparably for both women (8.6±1.8 METs vs. 5.6±1.8 METs respectively, p<0.00001) and men (8.7 ± 2.0 METs vs. 6.1 ± 1.8 METs respectively, p<0.00001). For every 1 MET decline in functional capacity, there was a significantly greater decline in QoL for men compared with women in physical health (4.0±1.1 vs. 2.9±0.3 days/month, P<0.001), mental health (2.4 ±1.2 vs. 1.8±0.3 days/month, P=0.001), and social health/recreational activities (4.1 ±1.0 vs. 2.9 ±0.3 days/month, P=0.0001), respectively (Figure 1). Conclusions: In an international INOCA survey, despite similar diagnoses, clinical comorbidities, symptoms, and quality of life, INOCA-related functional capacity declines are associated with a greater adverse impact on QoL in men compared to women. These findings highlight the need for future studies to include QoL measures in INOCA treatment strategies stratified by sex.